Interference of Chinese (L1) thinking mode in English (L2) argumentative essay writing of Malaysian Chinese students in UTAR - Xu, Hongru (2021)

(untitled)
Differences of English thinking mode and Chinese thinking mode interfere English learners whose first language is Chinese in their English as Second Language learning, especially when it comes to writing. This research aims to find out the differences in English writing of Malaysian Chinese students in UTAR between Chinese thinking mode influences and English thinking mode influences. At the same time, it also intends to find out the differences between ESL students in UTAR who are professionally trained and who are not in terms of the Chinese thinking mode interference. A pre-writing questionnaire and a written task of an argumentative essay are therefore applied to collect responses from twenty participants in UTAR, while 10 of them are from English majors and the other 10 are from non-English majors. The analysis shows that differences of English thinking mode and Chinese thinking mode in English writing can be spotted in grammar, sentence patterns, discourse development, and Chinglish elements. However, the differences in English writing between professionally trained English major and non-English major students appear in whether they can fulfill basic requirements of an argumentative essay, avoid types of grammar errors, and apply English logic sentence patterns and discourse development in the essays. Therefore, interference of Chinese thinking mode does exist in Malaysian Chinese students in UTAR who are still learning English.